Structural adjustments to the farm labour force, 1994-2011 : a Mincerian exploration of returns to education and experience - Pillay, Kavisha (School of Economics, 2015)
Agriculture is a vital source of employment and income for many unskilled workers in South Africa. However, due to the decline in the sector's contribution to Gross Domestic Product (GDP) (as a result of the reduction in agricultural production and an increase in the contribution of the manufacturing and services sectors) (Department of Agriculture, 2010), this vital role is diminishing. With changing economic conditions and the implementation of agricultural legislations, such as ESTA, most farm workers' living standards have decreased. Many farm workers earned significantly less than other unskilled workers therefore, to improve their wages, a minimum wage was introduced. However, the minimum wage only increased the wages of farm workers who were still employed as many were retrenched. Since the impact of the minimum wage on employment and wages has been thoroughly studied this paper seeks to determine whether the introduction of the statutory agricultural minimum wage, in 2003, restructured the agricultural labour force. The paper will use the Mincerian wage equation to estimate the returns to skills (education and experience) in order to determine if the productivity of farm workers was affected. The paper finds that educational attainment increased for farm workers and was rewarded by farmers, as the return to education increased. Experience increased for farm workers as well but was not rewarded accordingly, as there was a reduction in the return to experience. Therefore, farm owners prefer a more educated agricultural workforce to a more experienced workforce, as they are willing to offer higher wages to educated farm workers. Evidently, the minimum wage has restructured the workforce to be more productive, but since the same trends were seen for the control group, economic conditions also affected the agricultural workforce. The policy implications of this are that farmers discriminate against younger farm workers, which adds to the increasing youth unemployment problem in South Africa.